1993
DOI: 10.3758/bf03197979
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the memory code for temporal events induced by differential outcome expectancies in pigeons

Abstract: The effect of differential outcome expectancies on memory for temporal and nontemporal information was examined. Pigeons were trained to match short (2-sec) and long (8-sec) sample durations to red and green comparison stimuli, and vertical and horizontal lines to vertical and horizontal comparison stimuli. In Experiment 1, one differential outcome (DO) group received food for correct choices on short-sample trials, whereas another received food for correct choices on long-sample trials. On line-orientation tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…It is unlikely that the failure to obtain a significant chooseshort effect was due to a floor effect at delay intervals greater than zero. The delays used in the present experiment were similar to those which in other studies have consistently resulted in significant choose-short effects (Ducharme & Santi, 1993;Spetch, 1987;Spetch & Rusak, 1989;Spetch & Wilkie, 1983). In other studies, with similar delay intervals, accuracy on short -sample trials has been much higher than it was in the present experiment.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It is unlikely that the failure to obtain a significant chooseshort effect was due to a floor effect at delay intervals greater than zero. The delays used in the present experiment were similar to those which in other studies have consistently resulted in significant choose-short effects (Ducharme & Santi, 1993;Spetch, 1987;Spetch & Rusak, 1989;Spetch & Wilkie, 1983). In other studies, with similar delay intervals, accuracy on short -sample trials has been much higher than it was in the present experiment.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast to previous evidence that temporal information is coded in a retrospective and analogical fashion (Spetch & Sinha, 1989;Wilkie & Willson, 1990), the present research has identified an additional condition under which temporal information does not appear to be coded in this way. There are now three experimental procedures in which temporal samples are not retrospectively and analogically coded: the present MTO mapping conditions, successive MTS , and choice MTS in which temporal samples are associated with differential outcomes of food and no food (Ducharme & Santi, 1993). In addition, the present interference test results indicate that temporal summation effects are observed even when a choose-short effect has not been observed and most importantly even when the temporal target samples are preceded by color presampIes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation